A154 ASSESSING COLON SCREENING PROGRAM COLONOSCOPIES IN A NON-HOSPITAL ENDOSCOPY CLINIC. (26th February 2020) - Gillies, A N; Chow, R; Galorport, C; Macdonnell, C A; Yonge, J; Telford, J J; Rosenfeld, G; Bressler, B; Whittaker, S; Lam, E; Ramji, A; Enns, R A
Abstract: Background: Colorectal cancer is the most commonly diagnosed cancer in British Columbia, affecting 1 in 6 persons. The BC Colon Screening Program (CSP) screens individuals 50–74 years of age with biennial FIT (cut-off 10 mcg/g) with follow-up colonoscopy for positive results. In Vancouver, colonoscopies are performed in a hospital environment; however non-hospital endoscopy clinics have been used in other jurisdictions. Aims: To investigate the quality of procedure, rate of complications and need to repeat procedures in a hospital setting for colonoscopies performed on CSP patients in a non-hospital setting. Methods: A retrospective chart review for all CSP colonoscopies performed from 04/19 to 07/19 in a non-hospital endoscopy clinic. Data was collected from an electronic medical record system and included adenoma detection rates; any repeat procedures required in a hospital setting and adverse event rates. Criteria for a repeat in hospital colonoscopy were inadequate bowel preparation, body mass index exceeding the allowable threshold for a non-hospital colonoscopy and identification of a difficult to remove polyp such as a polyp > 20 mm or in a difficult location. Results: 801 FIT positive patients (ages 50–74) underwent colonoscopy in the non-hospital endoscopy clinic. The mean age was 60 years (51% female). The mean time between referral date and procedure date was 192 days. The neoplasia detection rate was 60.2%, there was one (0.1%) adverse event (post-polypectomy bleed) and 21 (2.6%) patients required a repeat colonoscopy in a hospital setting. Conclusions: Colonoscopy to follow-up a positive FIT in an non-hospital endoscopy clinic was safe and effective with a low number of repeat, in hospital colonoscopies required. Funding Agencies: None